JDBC : pocket reference. - Bales, Donald, ....- (Beijing : O'Reilly, 2003)
Samenvatting:The JDBC Pocket Reference offers quick look-ups for all methods of thestandard JDBC classes. These include concise reviews of the proceduresfor common JDBC tasks such as connecting to a database, executing storedprocedures, executing DDL and the like. You'll find documentation of theconnect string formats for the most common databases, including Oracle,SQL-Server, and PostgreSQL. You'll even find information on working withlarge objects, and on using SQL99 user defined datatypes to work withobject-relational data. Searching for this sort of material through largetutorials is frustrating and a waste of time, but this pocket-sized bookis easy to take anywhere and makes finding the information you need asnap
Keywords: Gegevensbanken; Java (programmeertaal).; Programmeren